To find the point of intersection of f(x) = x^2 + 2x-1 and the line y= 2x+3, we equate the two.

x^2 + 2x - 1 = 2x + 3

=> x^2 - 4 = 0

=> (x - 2)(x +2) = 0

x is equal to 2 and -2.

...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

To find the point of intersection of f(x) = x^2 + 2x-1 and the line y= 2x+3, we equate the two.

x^2 + 2x - 1 = 2x + 3

=> x^2 - 4 = 0

=> (x - 2)(x +2) = 0

x is equal to 2 and -2.

The corresponding values for y are 7 and -1

**Therefore the points of intersection are (2, 7) and ( -2, -1)**

Given the function f(x) = x^2 + 2x -1

and the line y= 2x+3

We need to find the intersection points for the curve and the line.

Then, we need to find the point that verifies f(x) and y.

==> f(x) = y

==> x^2 + 2x -1 = 2x +3

We will subtract 2x from both sides:

==> x^2 -1 = 3

Now we will add 1 to both sides.

==> x^2 = 4

==> x = +-2

Then, there are two points of intersection between the curve f(x) and the line y.

==> f(2) = 4+4-1 = 7

==> f(-2) = 4-4-1 = -1

**Then, the points of intersection are:**

**(-2, -1) and (2,7) **